Emerging cities and sustainable global environmental management: livelihood implications in the OIC countries - Abdulai, Abdul-Mumin; Siwar, Chamhuri (Academic Journals, 2009)
It is a fact that the majority of the world’s settlements are burgeoning into cities; especially at the turn of the 21st century, an era witnessing the emergence of new economies. Undoubtedly, cities play a pivotal role in the socio-economic, cultural and scientific development of all nations as chunk of global human development activities is planned and executed in the cities. In the same vein, deteriorated living conditions in the history of human habitat are conventionally noted to be largely associated with cities where grave environmental ‘atrocities’ are committed. Examples include urban sprawl, air and noise pollution, contaminated water sources, solid and liquid waste generation, environmentally related ill-health, etc. Many cities exist with their attendant environmental woes. Many more are emerging. What considerations (global partnership in forward planning, forecasting, concerted global social responsibility,etc) should be taken into account in order to sustain livelihoods in a somewhat healthy global environment? The paper explores this area with particular reference to the Organization of Islamic Conference member countries (OIC).